The Swedish PoliGraph - Rødven-Eide, Stian (University of Gothenburg, 2024)
An extensible knowledge graph with information on members of the Swedish parliament

En utvidgbar kunskapsgraf med information om Riksdagens ledamöter
The Swedish PoliGraph
Keywords: Language Technology (Computational Linguistics); knowledge graph; political science; swedish parliament; metadata; lexicon; Political Science; Statsvetenskap; Natural Language Processing; Språkbehandling och datorlingvistik